APPRAISAL ANALYSIS OF THE JAKARTA POST’S NEWS ARTICLE ON THE ENVIRONMENTAL ISSUE - Lestari, Yurike Ayu; Tallapessy, Albert; Murti, Ghanesya Hari (Universitas Islam Sumatera Utara (UISU), 2023)
This research discusses journalists' ideology and position in four selected news articles from the English-language newspaper, The Jakarta Post. The news articles report on the no-deforestation pledge of the 26th Conference of Parties (COP26), which commits to working collectively to halt and reverse forest loss and land degradation by 2030. This research aims to find the appraisal devices used by the journalist and explain the journalist's ideology and position toward the deforestation pledge. The revelation of ideology is analyzed through Appraisal System by Martin and White (2005). There are 90 sentences obtained in this thesis. The result shows that the three appraisal subsystems are applied in the texts. We found that the ideology of the journalists in two opposite sides. From four selected news articles, two news articles support the capitalist ideology, and the other supports the environmentally friendly ideology.